Evaluasi Pelaksanaan Kurikulum Berbasis HAM pada Sekolah Dasar - Penny Naluria Utami; Denny Zainuddin (Badan Strategi Kebijakan Hukum, 2010)
The Government needs to propose human rights-based education for all level of education, i.e. from Elementary School to the University. Human Rights education activities expected to become an integrated approach through daily activities of civil society. Human rights-based of education represent of continuing of the Decade for human rights education (1995-2004). Ministry of Education recommended to UNESCO proclaimed human rights-based education system for level of education. Human rights issues will be implemented into curriculum of education for elemantary and secondary level and integrated to religious subjects.